Strategi Memperkuat Integritas Lembaga Peradilan Indonesia - Sikti, Ahmad Syahrus (Judex Laguens, 2023)
Issues of the integrity of judges and judicial apparatus affect the quality of service, the reputation of the institution and the level of public trust. This means that the more integrity of judges and judicial apparatus in the law enforcement process, the fairer the verdicts handed down, the more quality services and the level of public trust increases. Integrity problems can be solved with a system approach, namely strengthening the internal supervision system which is both repressive and preventive.